Effect of ZnO nano-particulates on structure and properties of PZT/ZnO ceramics - Promsawat M. (2014)
In this research, effect of ZnO nano-particles on structure, mechanical and electrical properties of PZT ceramics was investigated. X-ray diffraction result suggested that tetragonality of PZT decreased with increasing ZnO content. Density tended to increase with an addition of ZnO while grain size of the ceramics decreased. An addition of ZnO increased hardness of the ceramics. Maximum hardness was achieved at an addition of 0.5 wt% ZnO. Within the PZT/ZnO ceramics, increasing content of ZnO gradually increased fracture toughness. Electrical properties characterization of the ceramics showed that an addition of ZnO reduced dielectric constant and slightly lowered Curie temperature. Ferroelectric measurement found that an addition of < 0.5 wt% ZnO did not significantly change ferroelectric properties. However, these properties were degraded at higher content of ZnO. Copyright © Taylor & Francis Group, LLC.